The Spiral of Violence: A Critical Analysis of The Genealogy of Islamophobia - Mohammad Fuyudun Niam Imam; Fawes Samudra; Muhammad Solahudin (Yayasan Pesantren Mahasiswa An-Nur, 2023)
The rise of terrorism by extremist groups with religious backgrounds and the development of Islamophobia in the West after 9/11 are essential issues that need to be addressed. After the WTC incident in 2001, the US declared a